2018
DOI: 10.1017/s204017441800017x
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational and early life influences on the well-being of Australian Aboriginal and Torres Strait Islander children: overview and selected findings fromFootprints in Time, the Longitudinal Study of Indigenous Children

Abstract: Footprints in Time: The Longitudinal Study of Indigenous Children (LSIC) is a national study of 1759 Australian Aboriginal and Torres Strait Islander children living across urban, regional and remote areas of Australia. The study is in its 11th wave of annual data collection, having collected extensive data on topics including birth and early life influences, parental health and well-being, identity, cultural engagement, language use, housing, racism, school engagement and academic achievement, and social and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 46 publications
(71 reference statements)
0
22
0
Order By: Relevance
“…Aboriginal and Torres Strait Islander people, one of the longest surviving civilisations in the world, make up 3% of the Australian population: that is over 700,000 people (Australian Institute of Health and Welfare 2015 ; Salmon et al 2019 ). Similar to other First Nation peoples globally impacted by colonisation, they face significant and ongoing health disparities, with a disease burden 2.3 times greater and life expectancy 10 years less than other Australians (Australian Institute of Health and Welfare 2015 ; Salmon et al 2019 ). This burden is reflected in a young age profile, where 34% of Aboriginal and Torres Strait Islander people are under 15 years of age compared to 18% of other Australians (Australian Institute of Health and Welfare 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Aboriginal and Torres Strait Islander people, one of the longest surviving civilisations in the world, make up 3% of the Australian population: that is over 700,000 people (Australian Institute of Health and Welfare 2015 ; Salmon et al 2019 ). Similar to other First Nation peoples globally impacted by colonisation, they face significant and ongoing health disparities, with a disease burden 2.3 times greater and life expectancy 10 years less than other Australians (Australian Institute of Health and Welfare 2015 ; Salmon et al 2019 ). This burden is reflected in a young age profile, where 34% of Aboriginal and Torres Strait Islander people are under 15 years of age compared to 18% of other Australians (Australian Institute of Health and Welfare 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Australia and internationally, community members, researchers, and increasingly governments have advocated for the use of strengths-based approaches, to counter the dominant deficit discourse in Indigenous health ( Durie, 2004 ; Fogarty, Lovell, Langenberg, & Heron, 2018 ; Foley & Schubert, 2013 ; Gray & Oprescu, 2015 ; Haswell-Elkins, Sebasio, Hunter, & Mar 2007 ; Laliberté, Haswell-Elkins, & Reilly, 2009 ; National Health and Medical Research Council, 2002 ; Smylie, Lofters, Firestone, & O'Campo, 2011 ; Wand & Eades, 2008 ). The intention of strengths-based approaches is not to ‘problem deflate’, misconstrue results, or deny inequities, but to refocus research and policy on identifying assets and strengths within individuals and communities and ‘avenues for action’ ( Bond, 2009 ; Fogarty, Lovell, et al, 2018 ; Foley & Schubert, 2013 ; Haswell-Elkins et al, 2007 ; Salmon et al, 2018 ; Wand & Eades, 2008 ). A 2018 review identified a typology of strengths-based approaches described in national and international literature about Indigenous peoples' health and wellbeing ( Fogarty, Lovell, et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…International research has identi ed signi cant strengths unique to Indigenous young people which help build and maintain resilience (33,34). One such strength is a particular a nity for creative technological innovation and design (15,35,36), and willingness to embrace empowerment and self-determination (1).…”
Section: Introductionmentioning
confidence: 99%